Isolated trochlear palsy as the only presentation of midbrain infarction: a case report - Wen-Ching Chen; Ying-Sheng Li; Poyin Huang (Journal of International Medical Research, 2021)
Trochlear palsy often results from traumatic, congenital and microvascular disorders. An intra-axial lesion as a cause of trochlear palsy is uncommon. Moreover, it usually accompanies other neurological deficits. Isolated trochlear palsy as the only presentation of brainstem stroke is unexpected. This current case report describes a 74-year-old male that presented with trochlear palsy without other neurological signs. Brain magnetic resonance imaging (MRI) revealed an acute midbrain infarction. The case report also reviews recent literature and provides a stepwise algorithm for clinicians to approach patients with trochlear palsy. Despite its rarity, clinicians are advised to consider ischaemic stroke as a cause of trochlear palsy even without other neurological deficits. Early MRI should be performed for prompt and proper management.